Pengaruh Komunikasi Internal Terhadap Kepuasan Kerja dalam Sebuah Organisasi: Studi Kasus Pt Xyz - Didier Neonisa (Bina Nusantara University, 2011)
Communication is an important element for all interactions among humans. In organization as the place people interacting and working together to reach the expected goal, communication will determine success or failure. People in organization are known as human resources. In other words, success in organization is determined by human resources factor. The research is purposed to learn communication role in increasing work satisfaction for human resources in PT XYZ. This research uses qualitative approach, therefore it is not too focus and being objective in data analyzing. Based on analysis result, it is concluded that in general every respondent agree that internal communication is going well in PT XYZ. Internal communication gives about 40% information needed to predict variations of work satisfaction.